25 Years with the 'Child' and the Archaeology of Childhood. (September 2015) - Lillehammer, Grete
<x content-type="archive" xml:space="preserve">Abstract</x> A presentation of the main points of the seminal article 'A child is born' from 1989, in particular with regard to the importance in the current trends and other issues not foreseen or perceived twenty-five years ago. In an effort to jumpstart debate in archaeology about the potential for a study of children in the past, the attempt was to define the child's world generally in time, space, and structure. It applied child's play as an analytical tool towards considering the child's world from an archaeological perspective. While the 'child' has matured itself, the field has contributed to the establishment of the archaeology of childhood as a subject of interest in research worldwide. Technological and methodological advancements have improved the abilities of archaeologists to study the worlds of children and childhood in past societies. The article touches upon some of these developments, and which show the points to have relevance today.